Beginning the principalship : a practical guide for new school leaders - Daresh, John C. 4 0 16; 5 (Thousand Oaks, California : Corwin Press, 2006)
Offers new school leaders guidance to help them survive their first year as principal, with advice on how to manage others' expectations, master the technical skills needed to run a school, create a personal professional growth plan, work with the community, incorporate staff in school goals, and work well with parents.
Includes bibliographical references.
Professional.
Keywords: 2 -- 0; 6; Administration -- First year school principals;School management and organization;Educational leadership;School superintendents and principals;Schools -- United States.;United States.;United States.;United States.;United States; 20; 2